Mechanical and thermal properties of SEBS-g-MA compatibilized halloysite nanotubes reinforced polyethylene terephthalate/polycarbonate/nanocomposites - Jamaludin, Nurul Ain (John Wiley and Sons Inc., 2015)
In this study, the effect of maleic anhydride grafted styrene-ethylene-butylene-styrene (SEBS-g-MA) content on mechanical, thermal, and morphological properties of polyethylene terephthalate/polycarbonate/halloysite nanotubes (PET/PC/HNTs) nanocomposites has been investigated. Nanocomposites of PET/PC (70: 30) with 2 phr of HNTs were compounded using the counter rotating twin screw extruder. A series of formulations were prepared by adding 5-20 phr SEBS-g-MA to the composites. Incorporation of 5 phr SEBS-g-MA into the nanocomposites resulted in the highest tensile and flexural strength. Maximum improvement in the impact strength which is 245% was achieved at 10 phr SEBS-g-MA content. The elongation at break increased proportionately with the SEBS-g-MA content. However, the tensile and flexural moduli decreased with increasing SEBS-g-MA content. Scanning electron microscopy revealed a transition from a brittle fracture to ductile fracture morphology with increasing amount of SEBS-g-MA. Transmission electron microscopy showed that the addition of SEBS-g-MA into the nanocomposites promoted a better dispersion of HNTs in the matrix. A single glass transition temperature was observed from the differential scanning calorimetry test for compatibilized nanocomposites. Thermogravimetric analysis of PET/PC/HNTs nanocomposites showed high thermal stability at 15 phr SEBS-g-MA content. However, on further addition of SEBS-g-MA up to 20 phr, thermal stability of the nanocomposites decreased due to the excess amount of SEBS-g-MA.